1991
DOI: 10.1254/jjp.57.79
|View full text |Cite
|
Sign up to set email alerts
|

Sugar-Specific Inhibitory Effects of Wheat Germ Agglutinin and Phytohemagglutinin-E4 on Histamine Release Induced by Basic Secretagogues from Rat Peritoneal Mast Cells and Their Possible Action Sites

Abstract: ABSTRACT-The histamine release induced by compound 48/80, bradykinin or polyethylenimine with a molecular weight of 600 (PEI6) was inhibited by wheat germ agglutinin (WGA) and phytohemagglutinin E-subunits (PHA-E4), and the inhibition was specifically reversed by N-acetyl glucosamine and N-acetyl galactosamine, respec tively. Concanavalin A (Con A) and phytohemagglutinin L-subunits (PHA-L4) did not inhibit the histamine release induced by compound 48/80, bradykinin or PEI6. The histamine release induced by sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
9
0

Year Published

1993
1993
2001
2001

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 28 publications
4
9
0
Order By: Relevance
“…In this study, we proposed that the binding of DSA to the corresponding glyco proteins resulted in histamine release and that WGA, STA and PWM inhibited it. These results were consistent with the inhibitory effects of lectins on the histamine release in duced by basic secretagogues (9,10). The binding of Con A to the glycoproteins including the IgE-IgE receptor complex, however, did not inhibit the histamine release induced by DSA, and a-MM, a haptenic sugar of Con A, was not inhibitory.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…In this study, we proposed that the binding of DSA to the corresponding glyco proteins resulted in histamine release and that WGA, STA and PWM inhibited it. These results were consistent with the inhibitory effects of lectins on the histamine release in duced by basic secretagogues (9,10). The binding of Con A to the glycoproteins including the IgE-IgE receptor complex, however, did not inhibit the histamine release induced by DSA, and a-MM, a haptenic sugar of Con A, was not inhibitory.…”
Section: Discussionsupporting
confidence: 85%
“…They lack responsiveness to non-immunologic stimuli, although they begin to respond to compound 48/80 after co-cul ture with fibroblasts (8). Recently we reported that a 10 min incubation of specific lectins with rat peritoneal mast cells resulted in the inhibition of the histamine release in duced by compound 48/80, bradykinin and PEI6 (9,10). The inhibitory lectins for the histamine release induced by compound 48/80, bradykinin or PEI6 were WGA (9), PHA-E4 (9) and STA (10), as well as MAM (10).…”
mentioning
confidence: 97%
“…Glycoproteins were detected by WGA and PHA-E4-blotting, but glycolipids were not (17). Because WGA and PHA-E4 are G1cNAc specific, especially the bisecting GIcNAc-specific lectins, glycoproteins with G1cNAc-residues seemed to be in volved in the histamine releasing mechanisms, and the binding of WGA and PHA-E4 to the glycoproteins result ed in inhibition of histamine release.…”
mentioning
confidence: 96%
“…Recently our group reported that a 10-min incubation of rat peritoneal mast cells with WGA or PHA-E4, but not with Con A or PHA-L4, resulted in sugar-specific inhi bition of the histamine release induced by compound 48/80, bradykinin and PEI6 (14,17). Glycoproteins were detected by WGA and PHA-E4-blotting, but glycolipids were not (17).…”
mentioning
confidence: 99%
“…Among the activators of the IgE-independent pathway, DSA is a lectin having affinity to GlcNAc oligomers. Moreover, our group observed that lectins with affinity to GlcNAc and /or sialic acid (Sia) inhibited histamine release induced by compound 48 / 80, substance P and DSA (5,11,12). On the other hand, the effects of D(+)Gal-, N-acetyl galactosamine (GalNAc)-and L(-)Fuc-specific lectins on the activation of mast cells induced by compound 48/80, substance P and DSA are unknown.…”
mentioning
confidence: 99%